Haemophilus influenzae type f meningitis in a previously healthy boy - Ronit, Andreas (BMJ Publishing Group, 2013)
Non-serotype b strains of Haemophilus influenzae are extremely rare causes of acute bacterial meningitis in immunocompetent individuals. We report a case of acute bacterial meningitis in a 14-year-old boy, who was previously healthy and had been immunised against H influenzae serotype b (Hib). The causative pathogen was identified as H influenzae serotype f (Hif), and was successfully treated with ceftriaxone. An immunological evaluation revealed transient low levels of immunoglobulins but no apparent immunodeficiency was found 2 years after the clinical insult.